Data security in cloud computing - Kumar, Vimal; Chaisiri, Sivadon; Ko, Ryan (The Institution of Engineering and Technology, 2017)
This one-stop reference covers a wide range of issues on data security in Cloud Computing ranging from accountability, to data provenance, identity and risk management.
Keywords: Cloud computing -- Security measures.; elektronické knihy; electronic books